HPLC Method for Determination of Thymol and Carvacrol in Thyme Tincture - Dedić, Mirza; Bečić, Ervina; Imamović, Belma; Žiga, Nermina; Medanhodžić-Vuk, Saira; Šober, Miroslav (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Genus Thymus contains about 300-400 species, many of which are used in traditional medicine. Thymus vulgaris (thyme) is the most commonly used Thymus. In official medicine, thyme is used as a general medicine for colds, flu, fever, coughing and bronchitis, such as: an antiseptic, spasmolytic, antifungicide, antitus, tonic, antihelmintic, antioxidant agent, antivirantic agent, carminative, sedative, diaforetic, antibacterial and as refresh remedy. The pharmacological effects of thyme are most closely related to its polyphenolic components, thymol and carvacrol. The most used chromatographic methods for determination of active compounds in herbal preparation is high-performance liquid chromatography. Results obtained by statistical processing are in the reference interval, which is  recommended by the ICH guidelines. By analyzing Thymi tincturae, it was found that the concentration of thymols was 0.807 mg/g of tincture, while the concentration of carvacrol was 0.082 mg/g tincture. This analysis is very fast, reliable and economical. The method does not require a complicated sample preparation and as such can be used in the regular control of the content of thymol and carvacrol in the finished product and the semi-product (tincture).